The role of cognitive emotion regulation strategies in depression, anxiety and stress of coronary heart disease patients - Solg, Zahra; Yaseminejad, Parisa (Researcher Bulletin of Medical Sciences, 2019)
Introduction: This study aims to examine the role of cognitive emotion regulation strategies in the degree of depression, anxiety, and stress of coronary heart disease patients by using predictive correlation method. Materials and Methods: In this research population consisted of all coronary heart disease patients who referred to Cardiovascular Specialized Hospital in Kermanshah city among whom 130 were selected as participants using available sampling method. Subsequently, they asked to complete Cognitive Emotion Regulation Questionnaire (CERQ) and Depression, Anxiety and Stress Scale (DASS-21). Collected data were analyzed using correlation matrix, multivariate analysis of variance (MANOVA) and hierarchical multiple regression analysis. Results: The MANOVA results showed that there was a significant difference between male and female patients (p< 0.05) in the strategies of rumination, positive refocusing, planning and positive reappraisal and blaming others. The results of correlation matrix showed that there was positive and significant relationship between inefficient components of self-blame, other-blame, rumination, and catastrophizing, and negative relationship between components of putting into perspective, positive refocusing, planning, and positive reappraisal with patients’ depression. In addition, the results of hierarchical multiple regression analysis indicated that among cognitive emotion regulation components, independent of gender, four components of self-blame, rumination, catastrophizing, and low positive reappraisal have great ability to predict depression, three components of self-blame, rumination, catastrophizing and planning are strong significant predictors of anxiety, and three components of self-blame, rumination and low positive reappraisal, respectively have the high ability to predict stress in coronary heart patients disease(p<0.05). Conclusion: According to the research results, the role of inefficient cognitive emotion regulation strategies in the degree of depression, anxiety, and stress of coronary heart disease patients have been demonstrated. Thus, teaching efficient cognitive strategies in setting up emotions to enhance the physical, psychological, and social health of coronary heart disease patients seems necessary.